2014
DOI: 10.1097/yco.0000000000000069
|View full text |Cite
|
Sign up to set email alerts
|

Polysubstance use

Abstract: Wide-ranging polysubstance use is more prevalent in subcultures such as 'ravers' (dance club attendees) and those already dependent on substances. Health risks are elevated in these groups. Research into the prevention and treatment of polysubstance use is underdeveloped. There may be benefit in targeting specific polysubstance use and risk profiles in prevention and clinical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
145
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(160 citation statements)
references
References 66 publications
12
145
0
3
Order By: Relevance
“…Respecto a la edad, datos en adultos jóvenes confirman relaciones con el policonsumo de sustancias (Ramo, Liu y Prochaska, 2012). Además, el policonsumo entre los jóvenes adultos se asocia a graves problemas como bajo desempeño a nivel cognitivo, problemas físicos, accidentes de tráfico, lesiones, enfermedades infecciosas y de transmisión sexual, suicidios, peleas y otros actos de violencia, además de poder llegar a convertirse en un patrón más permanente de consumo de varias sustancias (Connor, Gullo, White y Kelly, 2014;EMC-DDA, 2011Halley, Forster, Wood, Baezconde-Garbanati y Beth, 2014;Hughes et al, 2009;Mariño, Castro y Torrado, 2012;Trenz et al, 2012).…”
Section: Resumen Adicciones Vol 27 Nº 3 · 2015 Originalunclassified
“…Respecto a la edad, datos en adultos jóvenes confirman relaciones con el policonsumo de sustancias (Ramo, Liu y Prochaska, 2012). Además, el policonsumo entre los jóvenes adultos se asocia a graves problemas como bajo desempeño a nivel cognitivo, problemas físicos, accidentes de tráfico, lesiones, enfermedades infecciosas y de transmisión sexual, suicidios, peleas y otros actos de violencia, además de poder llegar a convertirse en un patrón más permanente de consumo de varias sustancias (Connor, Gullo, White y Kelly, 2014;EMC-DDA, 2011Halley, Forster, Wood, Baezconde-Garbanati y Beth, 2014;Hughes et al, 2009;Mariño, Castro y Torrado, 2012;Trenz et al, 2012).…”
Section: Resumen Adicciones Vol 27 Nº 3 · 2015 Originalunclassified
“…Although it has been shown that polydrug use may not always be problematic [17,18], considerable harm can be caused by it. For example, polydrug users are at an elevated risk for developing comorbid psychiatric and other health conditions [10] and polydrug use is also significantly related to social consequences [8]. Polydrug use can be very risky due to difficulties in dosing and unpredictable effects that substantially increase the number of deaths caused by overdose and other detrimental consequences of drug use [9,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…According to the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA), polydrug use has become a dominant pattern of drug use in Europe [4] and it has been brought up as a challenge in the formulation of the EU Drugs Strategy (2013-2020) [5]. Polydrug use is noted especially among problem drug users [6,7], but it needs to be recognized among the general population too due to its serious health and social consequences [8,9,10]. In the present literature, it is often claimed that polydrug use has increased during the last decades [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, mental health issues are more likely to be reported by poly-substance users (Salom, Betts, Williams, Najman, & Alati, 2016). This places young adults, among whom poly-substance use is common (Connor, Gullo, White, & Kelly, 2014), at a high risk. As such, groups who regularly use multiple substances are of public health concern (Bachhuber et al, 2016), despite many regarding their substance use as non-problematic.…”
Section: Introductionmentioning
confidence: 99%